Claude-Sonnet-4 Benchmark Performance Across Reasoning Mathematics Coding and Language Tasks - Assignee Research (Assignee Research, 2026)
This report synthesises findings from 16 peer-reviewed papers addressing the following research question: What are the benchmark performance scores of Claude-Sonnet-4 on reasoning mathematics coding and language understanding tasks. 12 claims were extracted from source literature; 2 were independently verified against retrieved documents. An automated multi-reviewer quality assessment produced a score of 4.4/10. This report is a machine-generated literature synthesis and does not constitute orig
Machine-generated literature synthesis.